Promoting Geographical Indication of Banyuwangi Liberoid Coffee: A Community Capital Framework - Danniary Ismail Faronny; Wenny Bekti Sunarharum; Luchman Hakim (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Promoting Geographical Indications (GI) for Liberica coffee in Banyuwangi is essential to enhance its recognition as a strategic economic commodity. This study aims to map communal assets using the Community Capital Framework (CCF) owned by coffee producers, supporting the development of GIs. Data was collected through on-site semi-structured questionnaires and interviews using a qualitative descriptive approach. The analysis, based on the CCF approach encompassing natural, cultural, human, social, political, financial, and built capital, allows for a comprehensive understanding of community resources. Integrating the CCF in promoting GI for Liberica coffee holds potential for sustainable development in Banyuwangi. Considering the seven key capitals (environmental, human, economic, infrastructure, social, cultural, and political) enables the formulation of a comprehensive strategy, ensuring product quality, market value, environmental sustainability, and the community's economic growth. By strengthening the Liberica coffee sector through the integration of CCF and GI promotion, the study facilitates heightened competitiveness, reputation, and market value, benefiting smallholder farmers and fostering overall economic growth. This approach aligns with the broader goals of sustainable development and contributes to the empowerment of the local coffee community in Banyuwangi.